Effect of pure iron interlayer on microstructure and properties of hot-rolled stainless steel clad plate. (September 2021) - Yu, Chao; Deng, Zejun; Liang, Shujie; Xiao, Hong; Zhao, Yunpeng
Abstract: Experiments on vacuum hot-roll bonding stainless steel clad plates with pure iron interlayers of different thicknesses were conducted at rolling temperatures of 1000 °C, 1100 °C, and 1200 °C and reduction ratios of 30 %, 50 %, and 70 %, respectively, to reduce the formation of brittle compounds at the bonding interface and improve the mechanical properties of the clad plates. The effects of pure iron interlayers with thickness of 1–3 mm on the microstructure and properties of the clad plates subjected to different rolling processes were studied via optical microscopy, scanning electron microscopy, and tensile-shear and tensile tests. Results showed that the carbon chromium compound layer near the interface could seriously reduce the mechanical properties of the clad plates. The pure iron interlayer could also effectively prevent the diffusion of carbon elements in carbon steel to stainless steel and prevent the generation of carbon chromium compounds. At 1100 ℃, 2mm pure iron could effectively inhibit the formation of compounds and obtain good mechanical properties. The maximum elongation was 53.8 % at 50 % reduction, and the shear strength and tensile strength were 318.2 and 501.8 MPa, respectively. When the reduction was 70 %, the elongation decreased to 30 %, but the shear strength and tensile strength peaked at 392 and 641.3 MPa, respectively.